The Gospel according to Jesus what does Jesus mean when He says, "Follow Me"? - MacArthur, John F. 1939- (Grand Rapids, MI Zondervan, 1988)
Includes bibliographical references.
Keywords: Faith (Christianity).; Obedience -- religious aspects -- Christianity